Modern survey sampling - Chaudhuri, Arijit
"Starting from the preliminaries through live examples, the author tells the story about what a sample intends to communicate to a reader about the unknowable aggregate in a real situation. The story develops its own logic and a motivation for the reader to put up with, herein follows. Various intellectual approaches are set forth, in as lucid a manner as possible. Developments reached hitherto are presented and reviewed. Certain fresh and unseen problems are also noted and possible solutions are hit upon"--